Pelatihan Dan Pendampingan Akuntabilitas Berbasis Digital Di Desa Cupak Kabupaten Jombang - Bella Dwi Ari Puspita K; Renata Maulita Wijaya; Anita Eka Pratiwi; Afifah Yusfi Rahmalia; Maylizza Putri Dyansyah (Universitas Muhammadiyah Manado, 2023)
Micro, small and medium enterprises (MSMEs) do not understand the importance of accountability, they have not been able to prepare financial reports based on financial accounting standards for micro, small and medium enterprises (SAK EMKM), and the use of digital technology in preparing financial reports has not been properly utilized by business actors. MSMEs. This community service activity aims to increase the perceptions of MSMEs in Cupak Village, Ngusikan District, Jombang Regency, East Java Province regarding the urgency of financial accountability for the business being carried out along with literacy in implementing SAK EMKM using digital, user-friendly accounting media. The method uses lectures, training and mentoring, the objects of community service activities are MSMEs actors in Cupak Village, Ngusikan District, Jombang Regency, East Java Province. The results achieved from this activity are increased understanding of the importance of business accountability and the implementation of financial records in accordance with SAK EMKM with user friendly digital accounting media. The mentoring fund training program makes MSMEs actors in Cupak Jombang understand the importance of accountability, this mentoring program makes MSMEs actors familiar with digital accounting information systems.